Reducing severe spasticity in cerebral palsy following meningoencephalitis by botulinum toxin (Medical Journal of Indonesia, 2017)
A 3-year-old boy diagnosed with diplegic cerebral palsy had received Botulinum toxin injection to reduce severe spasticity. There was an improvement of muscles tone and motor function including better ability of limb flexion of the knees and hip, adduction of the hip, flexion of the toes, and plantar flexion of the foot. No side effect was observed after the procedure.